Systematic review and meta-analysis of the safety of chloroquine and hydroxychloroquine from randomized controlled trials on malarial and non-malarial conditions - Souza Botelho, Mayra [UNESP]; Bolfi, Fernanda [UNESP]; Leite, Renata Giacomini Occhiuto Ferreira [UNESP]; Leite, Mauro Salles Ferreira [UNESP]; Banzato, Luisa Rocco [UNESP]; Soares, Luiza Teixeira [UNESP]; Olivatti, Thaina Oliveira Felicio [UNESP]; Mangolim, Amanda Sampaio [UNESP]; Oliveira, Flávia Ramos Kazan [UNESP]; Abbade, Luciana Patrícia Fernandes [UNESP]; Abbade, Joelcio Francisco [UNESP]; de Barros Almeida, Ricardo Augusto Monteiro [UNESP]; et al. (Springer Nature, 2021)
Background: Despite the expectations regarding the effectiveness of chloroquine (CQ) and hydroxychloroquine (HCQ) for coronavirus disease (COVID-19) management, concerns about their adverse events have remained. Objectives: The objective of this systematic review was to evaluate the safety of CQ and HCQ from malarial and non-malarial randomized clinical trials (RCTs). Methods: The primary outcomes were the frequencies of serious adverse events (SAEs), retinopathy, and cardiac complications. Search strategies were applied to MEDLINE, EMBASE, LILACS, CENTRAL, Scopus, and Trip databases. We used a random-effects model to pool results across studies and Peto’s one-step odds ratio (OR) for event rates below 1%. Both-armed zero-event studies were excluded from the meta-analyses. We used the Grading of Recommendations Assessment, Development, and Evaluation system to evaluate the certainty of evidence. Results: One hundred and six RCTs were included. We found no significant difference between CQ/HCQ and control (placebo or non-CQ/HCQ) in the frequency of SAEs (OR: 0.98, 95% confidence interval [CI]: 0.76–1.26, 33 trials, 15,942 participants, moderate certainty of evidence). However, there was a moderate certainty of evidence that CQ/HCQ increases the incidence of cardiac complications (RR: 1.62, 95% CI: 1.10–2.38, 16 trials, 9908 participants). No clear relationship was observed between CQ/HCQ and retinopathy (OR: 1.63, 95% CI: − 0.4–6.57, 5 trials, 344 participants, very low certainty of evidence). Conclusions: CQ and HCQ probably do not increase SAEs, with low frequency of these adverse events on malarial and non-malarial conditions. However, they may increase cardiac complications especially in patients with COVID-19. No clear effect of their use on the incidence of retinopathy was observed. Systematic review registration: PROSPERO CRD42020177818.
Keywords: Adverse effects; Chloroquine; COVID-19; Hydroxychloroquine; Safety; Systematic review